Step-by-step Solution

Solve the quadratic equation $x^2-x+1=0$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Final Answer

$x=\frac{1+\sqrt{-3}}{2},\:x=\frac{1-1\cdot \sqrt{-3}}{2}$

Step-by-step explanation

Problem to solve:

$x^2-x+1=0$
1

To find the roots of a polynomial of the form $ax^2+bx+c$ we use the quadratic formula, where in this case $a=1$, $b=-1$ and $c=1$. Then substitute the values of the coefficients of the equation in the quadratic formula:

  • $\displaystyle x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}$

$x=\frac{1\pm \sqrt{-3}}{2}$
2

To obtain the two solutions, divide the equation in two equations, one when $\pm$ is positive ($+$), and another when $\pm$ is negative ($-$)

$x=\frac{1+\sqrt{-3}}{2},\:x=\frac{1-1\cdot \sqrt{-3}}{2}$

Final Answer

$x=\frac{1+\sqrt{-3}}{2},\:x=\frac{1-1\cdot \sqrt{-3}}{2}$
$x^2-x+1=0$

Main topic:

Quadratic equations

Related formulas:

1. See formulas

Time to solve it:

~ 0.03 s (SnapXam)